2023
DOI: 10.4253/wjge.v15.i8.528
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound artificial intelligence-assisted for prediction of gastrointestinal stromal tumors diagnosis: A systematic review and meta-analysis

Rômulo Sérgio Araújo Gomes,
Guilherme Henrique Peixoto de Oliveira,
Diogo Turiani Hourneaux de Moura
et al.

Abstract: BACKGROUND Subepithelial lesions (SELs) are gastrointestinal tumors with heterogeneous malignant potential. Endoscopic ultrasonography (EUS) is the leading method for evaluation, but without histopathological analysis, precise differentiation of SEL risk is limited. Artificial intelligence (AI) is a promising aid for the diagnosis of gastrointestinal lesions in the absence of histopathology. AIM To determine the diagnostic accuracy of AI-assisted EUS in diagnosing SELs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These included 10 studies pertaining to upper gastrointestinal endoscopy[ 9 , 18-26 ], 5 studies focusing on colonoscopy [ 27-31 ], and 4 studies on capsule endoscopy [ 32-35 ]. Additionally, there was 1 study about endoscopic ultrasound (EUS) and 1 study about laryngoscopy [ 36 37 ]. Detail can be seen in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…These included 10 studies pertaining to upper gastrointestinal endoscopy[ 9 , 18-26 ], 5 studies focusing on colonoscopy [ 27-31 ], and 4 studies on capsule endoscopy [ 32-35 ]. Additionally, there was 1 study about endoscopic ultrasound (EUS) and 1 study about laryngoscopy [ 36 37 ]. Detail can be seen in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In a recent meta-analysis involving eight retrospective studies including 2,355 patients, AI-assisted EUS models demonstrated a sensitivity of 92% (95% CI, 89-95%), specificity of 80% (95% CI, 75-85%), and AUC value of 0.949 for diagnosing GISTs [16]. However, experienced endoscopists demonstrated a sensitivity of 72% (95% CI, 67-76%), specificity of 70% (95% CI, 64-76%), and AUC value of 0.777 for diagnosing GISTs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, EUS is regarded as the most valuable diagnostic tool for evaluating gastric SETs. However, the diagnosis of SETs by EUS is operator-dependent; thus, interobserver variability and sometimes intraobserver variability are major limitations [12][13][14][15][16]. Accordingly, tissue acquisition using EUS guide, such as EUS-guided fine-needle aspiration (EUS-FNA) and EUS-guided fine-needle biopsy (EUS-FNB), is employed to establish a definitive histopathological diagnosis in patients with SETs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation